Design and simulation double Ku-band Vivaldi antenna - Huda Ibrahim Hamd; Israa Hazem Ali; Ahmed Mohammed Ahmed (Institute of Advanced Engineering and Science, 2022)
Due to the tremendous development in the field of wireless communication and its use in several fields, whether military or commercial was proposed. A novel tapered slot Vivaldi antenna is designed and simulated at double band frequency (Ku-band) using computer simulation technology (CST) software 2020. The dimensions of the antenna are 2.3 × 1 × 0.4 mm3 with a microstrip feed of 0.5 mm. The proposed antenna is improved by cutting a number of circle shapes on the patch layer in different positions. The simulation results are divided into more sections according to the number of circle shapes cutting. The results are good acceptance and make the improved Vivaldi antenna valuable in many future wireless communication applications.